Optimization of current total harmonic distortion on three-level transformerless photovoltaic inverter - Ismail, Daut, Prof. Dr.; Muhammad Irwanto; Mohd Irwan, Yusoff; Gomesh Nair, Shasidharan; Noor Syafawati, Ahmad (Elsevier Ltd., 2013)
Link to publisher's homepage at http://www.elsevier.com/